A Rapid Mercury Droplet Electrode Polarography Method for Determination of Blood Lead Level in Lead Poisoned People - Hosseini, Golriz; Hanaie, Jalal; Ostadi, Ali; Valipor, Javad; Hamidi, Aliasghar; Ghanbarzadeh, Saeed (Drug Research, 2020)
Background Lead is a hazardous heavy metal, which causes many problems in the human body. Unfortunately, recent reports showed that smugglers and opium sellers add lead to drugs during the production procedure in order to increase its weight and cost.Purpose The aim of this study was development of a rapid and accurate method for measurement of blood lead levels (BLL) in the oral and inhaled opiate abuser people.Methods BLL in samples obtained from the oral and inhaled opium addicted patients referring to Sina Hospital in Tabriz, Iran, during 2017 was compared with healthy control group (N=15). The wet digestion method was used to prepare whole blood and Mercury Droplet Electrode Polarography (MDEP) method was utilized for measurement of the lead content of digested samples.Results Results showed that there were significant differences between the BLL of samples obtained from oral (17.12±74.61 μg/dL, p<0.0003) and inhaled (19.33±2.257 μg/dL, p<0.0001) opium addicted groups in comparison with healthy control group (4.669±0.3367 μg/dL).Conclusion Based on the results of this study it was observed that BLL in opium addicted people needs to be measured as soon as possible. Furthermore, screening of blood lead concentrations in opium-addicted people with a rapid and accurate MDEP method is very necessary and important.
Keywords: chemistry; diagnostics; drug dependence; drugs of abuse; toxicology